2014
DOI: 10.1111/lre.12071
|View full text |Cite
|
Sign up to set email alerts
|

Use of geographical information system and remote sensing techniques for planning culture‐based fisheries in non‐perennial reservoirs of Sri Lanka

Abstract: The presence of a wide areal extent of small‐sized village reservoirs offers a considerable potential for the development of culture‐based fisheries (CBFs) in Sri Lanka. To this end, this study uses geographical information systems (GISs) and remote sensing (RS) techniques to determine the morphometric and biological characteristics most useful for classifying non‐perennial reservoirs for CBF development and for assessing the influence of catchment land‐use patterns on potential CBF yields. The reservoir shore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Comparison of gross income (GI) and profits per annum from downstream paddy cultivation and culture-based fisheries (CBF) in Ampara wewa, Hambegamuwa and Aluthdiulwewa during2012- 2014 (after Pushpalatha et al 2017 …”
mentioning
confidence: 99%
“…Comparison of gross income (GI) and profits per annum from downstream paddy cultivation and culture-based fisheries (CBF) in Ampara wewa, Hambegamuwa and Aluthdiulwewa during2012- 2014 (after Pushpalatha et al 2017 …”
mentioning
confidence: 99%
“…Index of evenness was inverse to index of diversity so that the higher evenness was a temporary area. This opinion was supported by Wijenayake et al (2014); Chandrasoma and Pushpalatha (2018) that revealed the high index of diversity indicated that at this location it was feasible in terms of the availability of natural food for inland fisheries activities. On the other hand, temperature, sunlight, dissolved oxygen and pH were important components of plankton life and growth in various inundation.…”
Section: Discussionmentioning
confidence: 72%
“…TSI (SD) = 60 -14.41 ln Secchi disk (metres) TSI (Chl) = 9.81 ln chlorophyll-a (mg/m 3 ) + 30.6 TSI (TP) = 14.42 ln total phosphorus (mg/m 3 ) + 4.15 Jayasinghe et al (2005) observed that in nonperennial reservoirs of Sri Lanka TSI (TP) = TST (SD) > TSI (SD) showing non-algal particles dominate light attenuation. Jayasinghe et al (2005) and Wijenayake et al (2014) also showed that CBF yields in non-perennial reservoirs of Sri Lanka were positively correlated to chlorophyll-a content. Furthermore, the ratio of forest cover plus scrubland cover in the catchment area to reservoir extent was also found to be significantly related to the chlorophyll-a content and the CBF yield (Wijenayake et al 2014).…”
Section: Limnological Aspectsmentioning
confidence: 87%
“…Jayasinghe et al (2005) and Wijenayake et al (2014) also showed that CBF yields in non-perennial reservoirs of Sri Lanka were positively correlated to chlorophyll-a content. Furthermore, the ratio of forest cover plus scrubland cover in the catchment area to reservoir extent was also found to be significantly related to the chlorophyll-a content and the CBF yield (Wijenayake et al 2014).…”
Section: Limnological Aspectsmentioning
confidence: 87%